Holding UNPOL to account : individual criminal accountability of United Nations police personnel - Kihara-Hunt, Ai (International humanitarian law series ;, 2017)
Ai Kihara-Hunt's Holding UNPOL to Account: Individual Criminal Accountability of United Nations Police Personnel analyzes whether the mechanisms that address criminal accountability of United Nations police personnel serving in peace operations are effective, and if there is a problem, how it can be mitigated. The volume reviews the obligations of States and the UN to investigate and prosecute criminal acts committed by UN police, and examines the jurisdictional and immunity issues involved. It concludes that these do not constitute legal barriers to accountability, although immunity poses some problems in practice. The principal problem appears to be the lack of political will to bring prosecutions, as well as a lack of transparency, which makes it difficult accurately to determine the scale of the problem.